Pengaruh budaya instan terhadap perilaku keuangan Gen Z: Studi pada kesadaran risiko dan pemanfaatan bank syariah - Sholikhah, Laila Mar’atus (Maliki Interdisciplinary Journal, 2025)
The digital era has formed an instant culture that greatly influences the mindset and behavior of Generation Z (Gen Z), especially in long-term decision making. Instant culture encourages the desire for quick results and instant gratification, which has an impact on low long-term risk awareness, especially in financial behavior. This study aims to examine the characteristics of instant culture among Gen Z and its implications for financial planning, risk management, and interest in Islamic financial services. Through a descriptive-qualitative approach with literature analysis, it was found that instant culture contributes to impulsive consumption patterns, minimal financial planning, and psychological stress due to expectations of instant success. However, there is an opportunity that Islamic financial values ​​such as fairness, transparency, and sustainability can be an alternative solution in shaping the financial behavior of Gen Z to be more risk-aware and long-term oriented. The results of this study are expected to be a reference in developing an Islamic financial literacy strategy that is adaptive to the digital and psychological characteristics of Gen Z.